Sistema de gestión de evaluaciones en el centro de idiomas de la ESPAM MFL. - Gilces Vera, Eliana Lisbeth (2017)
The work described shows the results of the evaluation management system, implemented in the Language Center of the Escuela Superior Politécnica Agropecuaria de Manabí, the system generates the evaluations and it qualifies them through the Optical Mark Recognition (OMR) which examines the answers of the students. Inductive and Deductive methods were used through the observation technique and making interviews that allowed the collection and analysis of the information. We used the agile SCRUM methodology for the development of software that consists of three stages: in stage one we performed the product list (Product Backlog), we planned the sprints with their respective functional requirements, in stage two was carried out the development of the sprints and in stage three tests of black box to validate the correct operation of the system. It was used as a Visual Studio 2012 development tool and within it was used the VB.NET programming language, and as a SQL Server database manager system. The results show that the system allows to reduce the time dedicated to these processes.